Adaptive Coding and Modulation for Satellite Communication Links in the Presence of Channel Estimation Errors - Weerackody, Vijitha (MILCOM IEEE Military Communications Conference, 2013)
Adaptive coding and modulation (ACM) schemes are very useful in satellite communication systems because they provide variable coding rates and modulation levels that can be used under different channel gain conditions. The effectiveness of the ACM scheme depends on the accuracy of the channel estimates. Because channel estimation plays a key role in ACM schemes, we present an estimation technique for the channel SNR. Furthermore, because channel SNR estimates are unreliable, we modify the ACM scheme to incorporate channel estimation errors. It is shown that this scheme significantly improves the performance of the ACM scheme.